NMR analysis and triad sequence distributions of poly(3-hydroxybutyrate-co-3-hydroxyvalerate). (October 2020) - Cheng, H.N.; Biswas, Atanu; Vermillion, Karl; Melendez-Rodriguez, Beatriz; Lagaron, Jose Maria
Abstract: Polyhydroxyalkanoates (PHAs) are considered promising "green" alternatives to synthetic polymers because they are bio-derived, biodegradable and biocompatible. The properties of bacterial PHA copolymers depend on their microstructures, which can be modified with the use of different fermentation processes and feed materials. Thus, it is desirable to have an improved testing method for the determination of PHA microstructures. In this work, a detailed NMR analysis of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) microstructure was made. Previously only two of the hydroxyvalerate 13 C NMR peaks have been assigned at the triad level. In this work, three of the 13 C hydroxyvalerate peaks and two of the hydroxybutyrate peaks were found to be split into four peaks each due to comonomer sequence effects. Using eight copolymer samples with a wide compositional range, we were able to assign all these peaks to B-centered and V-centered triad sequences. Through curve deconvolution, the triad intensities were determined. These triad sequence intensities can then be analyzed via both the first-order Markovian and two-component Bernoullian models to obtain more in-depth information on copolymer composition and comonomer reactivities. Highlights: A detailed microstructural analysis of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) was made with solution NMR. New 13 C spectral assignments at the triad level for this copolymer were made. Quantitative 13 C NMR sequence data on eight copolymer samples were obtained through curve deconvolution. The data were fitted to both one-component and two-component statistical models. This improved NMR methodology should be useful in differentiating samples made with different processes.